2020
DOI: 10.1097/mnm.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Global brain glucose uptake on 18F-FDG-PET/CT is influenced by chronic cardiovascular risk

Abstract: Purpose:The goal of this study was to assess global cerebral glucose uptake in subjects with known cardiovascular risk factors by employing a quantitative 18 F-fluorodeoxyglucosepositron emission tomography/computed tomography (FDG-PET/CT) technique. We hypothesized that at-risk subjects would demonstrate decreased global brain glucose uptake compared to healthy controls. Methods:We compared 35 healthy male controls and 14 male subjects at increased risk for cardiovascular disease (CVD) as assessed by the Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…These data confirm and expand on the results from a previous study on a small middle-aged cohort, 23 and on our cross-sectional findings in the same PESA cohort in which higher cardiovascular risk was associated with lower cerebral glucose metabolism. 11 They are also in line with reports from older longitudinal cohorts of cognitively intact individuals, 24 but go one step further by showing that the decline in cerebral glucose consumption starts earlier, during midlife.…”
Section: Discussionsupporting
confidence: 92%
“…These data confirm and expand on the results from a previous study on a small middle-aged cohort, 23 and on our cross-sectional findings in the same PESA cohort in which higher cardiovascular risk was associated with lower cerebral glucose metabolism. 11 They are also in line with reports from older longitudinal cohorts of cognitively intact individuals, 24 but go one step further by showing that the decline in cerebral glucose consumption starts earlier, during midlife.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the patients with hypoxic COPD showed greater severity of cerebral hypoperfusion and cognitive decline than patients with non-hypoxic COPD or age-matched healthy participants; furthermore, hypoperfusion correlated with the results of neuropsychological tests [17]. Moreover, a recent study by Borja et al [18] reported that impaired blood flow to the brain causes a decrease in global brain glucose uptake on FDG PET/CT. Therefore, the reduction in brain glucose uptake in our study could be due to overall decreased blood flow rather than specific Alzheimer’s disease-like neurodegenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of FDG in August 1976 opened a new era in medical imaging and has had a major impact on the management of many diseases and disorders over the past four decades (106). While early investigation demonstrated its role in neuropsychiatric disorders, over the years, this tracer has been shown to be effective in detecting a variety of common human diseases including cancer, inflammation, and metabolic abnormalities (107)(108)(109). Due to the lack of total-body PET imaging capabilities in the 1970s and 80s, most research studies that were conducted early on in the development of this modality dealt with brain disorders.…”
Section: Discussionmentioning
confidence: 99%